Corneal densitometry changes post-CXL for keratoconus: Comparative evaluation of epithelium-off, contact lens-assisted, and transepithelial techniques - Barkha Gupta; Chintan Malhotra; Supriya Dhar; Khushdeep Abhyapal; Arun K. Jain; Amit Gupta (Indian Journal of Ophthalmology)
Purpose: To evaluate changes in corneal backscattering after collagen cross-linking (CXL) for progressive keratoconus and compare its course with different techniques – standard epithelium-off CXL (SCXL), contact lens-assisted CXL (CACXL), and transepithelial CXL (TECXL). Setting: Advanced Eye Center, Post Graduate Institute of Medical Education and Research, Chandigarh, India. Design: Retrospective comparative study. Methods: Ninety-four eyes (SCXL: 47, CACXL: 30, and TECXL: 17) were compared. Corneal haze was quantified using Scheimpflug tomography, pre- and post-CXL at 1, 3, 6, and 12 months. Results: The baseline mean density score of the central anterior stromal layer was 16.14 ± 7.07, 15.85 ± 7.89 and 15.89 ± 7.21 in SCXL, CACXL, and TECXL groups, respectively (P 0.93). After SCXL, the score increased to 28.83 and 31.34 at 1 and 3 months, respectively (both P < 0.001) and dropped at 6 months (28.66, P < 0.001) and 12 months (23.72, P 0.003). Post-CACXL, the mean densitometry peaked at 3 months (20.35, P 0.14) and returned toward baseline at 6 months (18.82, P 0.15). After TECXL, it increased slightly at 1 month (18.47, P 0.17), decreased at 3 months (14.88, P 0.7), and plateaued over 1 year. No correlation with visual acuity was seen. Conclusion: Corneal haze increased significantly after SCXL, peaking at 3 months, declining over 6–12 months, and returning to baseline at 12 months. In contrast, post-TECXL and -CACXL, there was an insignificant increase in anterior corneal haze, which returned to baseline within 3–6 months.